2014
DOI: 10.1371/journal.pone.0090874
|View full text |Cite
|
Sign up to set email alerts
|

External Error Monitoring in Subclinical Obsessive-Compulsive Subjects: Electrophysiological Evidence from a Gambling Task

Abstract: BackgroundFeedback-related negativity (FRN) is believed to be an important electrophysiology index of “external” negative feedback processing. Previous studies on FRN in obsessive-compulsive (OC) individuals are scarce and controversial. In these studies, anxiety symptoms were not evaluated in detail. However, OC disorders have a number of radical differences from anxiety disorders. It is necessary to study FRN and its neuroanatomical correlates in OC individuals without anxious symptoms.MethodsA total of 628 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 78 publications
(115 reference statements)
1
17
0
2
Order By: Relevance
“…Thus, the internal consistency of a measure also puts a ceiling on how much true score is available to be associated with other variables (e.g., clinical correlates). The RewP, FN, and ΔRewP have all been examined as potential candidate biomarkers of various forms of psychopathology, including depressive symptoms, anxiety symptoms, and behavioral problems (Bress et al, ; Foti & Hajcak, ; Kessel et al, ; Kessel, Kujawa, Hajcak Proudfit, & Klein, ; Thoma, Edel, Suchan, & Bellebaum, ; Zhu et al, ). The most established and replicated of these associations is between depressive symptoms and the RewP or ΔRewP, but not the FN (Bress et al, ; Foti & Hajcak, ; Foti, Kotov et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the internal consistency of a measure also puts a ceiling on how much true score is available to be associated with other variables (e.g., clinical correlates). The RewP, FN, and ΔRewP have all been examined as potential candidate biomarkers of various forms of psychopathology, including depressive symptoms, anxiety symptoms, and behavioral problems (Bress et al, ; Foti & Hajcak, ; Kessel et al, ; Kessel, Kujawa, Hajcak Proudfit, & Klein, ; Thoma, Edel, Suchan, & Bellebaum, ; Zhu et al, ). The most established and replicated of these associations is between depressive symptoms and the RewP or ΔRewP, but not the FN (Bress et al, ; Foti & Hajcak, ; Foti, Kotov et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The question of whether anxiety moderates the relationship between OC symptoms and decision-making is one that will be addressed in the current study. Since researchers have found executive functioning deficits that indicate orbitofrontal impairment in nonclinical samples who score highly on OC measures (e.g., Spitznagel & Suhr, 2002; Zhu et al, 2014), this study will employ a non-clinical sample.…”
mentioning
confidence: 99%
“…The most used task for the assessment of decision-making was the Iowa Gambling Task and all studies that used this test suggested that decision-making might qualify as an endophenotype for OCD. 23 , 51 , 54 - 56 An interesting issue is that, in the study of da Rocha et al (2008), 54 this neuropsychological function was also associated with the presence of the polymorphism of the serotonin transporter gene and verified that those with the short allele (s/Lg), i.e. low expression function, performed significantly worse on the test.…”
Section: Discussionmentioning
confidence: 94%
“…The deficits/impairments most frequently found in OCD, were related to the following abilities: behavioral reversal/alternation, 50 , 51 set-shifting/cognitive flexibility, 50 , 52 , 53 decision making, 23 , 51 , 54 - 56 response inhibition, 20 , 50 , 52 , 53 , 57 , 58 planning, 23 , 55 , 59 reversal learning, 60 spatial working memory 59 , 61 and sustained attention. 57 For a deeper analysis of the results found in the systematic review, the neuropsychological instruments were grouped in the Discussion section according to the components of executive function evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation